KONTRIBUSI PAJAK REKLAME DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH DI KOTA SUNGAI PENUH TAHUN 2013-2017 - Heppi Syofya (LPPM - STIE SAKTI ALAM KERINCI, 2020)
This study aims to determine the contribution of advertisement tax in increasing regional original income in Sungai Penuh City in 2013-2017. Advertising tax is a tax on the implementation of billboards, while billboards are objects, tools, manufacture, or media according to the variety of shapes and patterns for commercial purposes and are used to introduce, recommend or positively introduce an item, service, or person, or, to attract general attention to an item, service or person placed or can be seen, read, or heard from a place by the public in Sungai Penuh City, except those carried out by the government. Average advertisement tax contribution in increasing the original revenue of the Sungai Penuh City area by 0.968% with unfavorable criteria. Advertising tax is not a major contributor to increasing the original income of the Sungai Penuh City area